Level of modernization of the National Water Laboratory from 1997 - Mora-Alvarado, Darner (2024)
The current facilities of the National Water Laboratory (LNA) date back to 1921. Despite the limitations in the physical infrastructure of the LNA headquarters, this study presents the level of modernization available considering the equipment. , human resources and comparative advances in the accreditation processes of the quality management system, inspections and analytical techniques with the INTE/ISO/IEC 17025:2017 and INTE/ISO/IEC 17020:2012 standards, from the designation of the AyA Central Laboratory as a National Water Laboratory, through Executive Decree No. 26066-S from 1997.